Association between daily living activities and quality of life in post-COVID-19 patients: a cross-sectional study - Shameem Ahammad; Ruksana Akter; Md. Abdul Koddus; Md. Kabir Hossain; Ehsanur Rahman; Tofajjal Hossain; Mohammad Mohinul Islam; Khin Nyein Yin; Md. Feroz Kabir; Md. Iqbal Kabir Jahid (Discover Public Health)
Abstract Background The COVID-19 pandemic has resulted in a significant increase in instances of post COVID-19 condition (PCC), which is defined by enduring symptoms that impact all facets of everyday life. After the acute period of COVID-19, many people still face considerable difficulties in carrying out activities of daily living (ADLs), which are essential for independent functioning and overall quality of life (QoL). Objective This study aimed to prompt how these persistent symptoms affect individuals’ ability to perform ADLs-basic tasks essential for self-care and daily functioning and how these limitations, in turn, influence overall QoL. Methods This cross-sectional study was conducted on 2054 individuals who were previously diagnosed COVID-19 and aged between 18 to 70 years old. Excluding those with severe neurological or psychiatric conditions, cognitive impairment, critical illness, or those not meeting PCC criteria per WHO working group criteria. We used questionnaires that considered demographic and socioeconomic data, activities of daily living, and quality of life, which were measured using the Modified Barthel ADL index (MBI) and WHOQOL-BREF questionnaire. The interactions of all data and the scores of MBI and WHOQOL-BREF were analyzed. Pearson correlation coefficient analysis was applied to the association between four WHOQOL-BREF domains with a total MBI score. Data were analyzed using independent t-test analyses. Result Out of the total participants, 911 individuals (44.35%) had signs of post-COVID-19 conditions. The average age of these individuals was 39.62 ± 11.4 years. PCC cases exhibited significantly lower QoL scores than asymptomatic cases across all WHOQOL-BREF domains: physical health (p < 0.001), psychological health (p < 0.001), social relationships (p < 0.001), and environmental health (p < 0.001). A positive correlation was found between physical health and social relations (r = 0.070, p < 0.05), psychological health and social relations (r = 0.130, p < 0.01), and environmental health and social relations (r = 0.084, p < 0.05). We discovered a weak and non-significant inverse relationship between the Modified Barthel ADL Index’s total score and most of the WHOQOL Brief domains (p > 0.05). Conclusion Our study concludes that approximately 45% of subjects displayed symptoms of post-COVID-19 disorders, with an average age of almost 40. Our study reveals a slight inverse correlation between the scores of the Modified Barthel Index and most domains of the WHOQOL Brief despite the high occurrence of these symptoms. According to the WHOQOL Brief questionnaire, the degree of functional impairments following COVID-19 significantly impacted the perceived quality of life in this study. Future research could be enhanced by investigating supplementary factors and utilizing longitudinal methodologies to comprehend the intricate interaction between post-COVID-19 syndrome and outcomes related to quality of life.